Furnish : furniture and interior design for the 21st century. - Lovell, Sophie, ....- (Berlin : Gestalten, 2007)
The occupation of space is a trend that can currently be recognized in many creative fields. While furniture and product design were once largely driven by classical industrial and interior design, these disciplines are now also being shaped by the visual culture of graphic design and high-tech production processes. These new influences are contributing to the creation of furniture and interiors that go beyond anything previously designed or imagined. Furnish presents domestic territories that expand upon our current understanding of interior design. The book documents recent work by designers, artists and architects that shows how they are using furniture in pioneering ways: as environment, as art object, as digital-organic growth, as mutation or as insertion. These cutting-edge examples are a sure indicator of the trends that will be influencing interiors as well as hotel, restaurant and club design for the next several years. Furnish also explores the new hybrid nature of occupied spaces, where the domestic enters the realm of fine art and where objects from pimped heirlooms to rapid prototypes find their homes. The book also presents surprising interdisciplinary work, for example, the results of architects engineering tables, graphic designers creating soft furniture and industrial designers making concept art. The experimental spaces that are shown in Furnish are not only interesting for interior designers, but also contain innovative examples of interdisciplinary design work that are relevant and inspiring for anyone working creatively.
Keywords: Ontwerpen